Correlation of kidney size with kidney function and anthropometric parameters in healthy subjects and patients with chronic kidney diseases - Jovanovi, Dijana; Gasic, Branislav; Pavlovic, Stevan; Naumovic, Radomir (Renal failure, 2013)
Abstract Background/Aim: Echosonography is a simple, noninvasive method of kidney visualization. The objective of this study was to compare the kidney echosonograpic characteristics with the kidney function and anthropometric characteristics in healthy subjects and patients with the chronic kidney disease (CKD). Methods: The study involved 49 patients (21 men; 46.02 ± 14.27 years) with CKD and the control group of 46 healthy persons (20 males; 45.45 ± 18.48 years). Physical examination, kidney echosonography and laboratory analyses including creatinine clearance (Ccr; 24 h and calculated by Cockroft--Gault (C--G) formula) were done in all persons. Results: There was no significant difference in age and sex between two groups but serum creatinine concentration was significantly higher (218.8 vs. 84.5 μmol/L) and Ccr significantly lower (66.44 vs. 94.20 mL/min, C--G) in patient group. The left kidney was larger in both groups, but the only significant difference was in kidney depth (p < 0.01). There was significant correlation between all measured kidney dimensions, volume, parenchymal thickness and serum creatinine concentration and Ccr (C--G) in patient group. In the controls, there was no significant correlation between the kidney size and function, but there was a significant correlation between the kidney width, depth, volume and patients' age and anthropometric parameters. On the contrary, all analyzed parameters of kidney size, except volume, did not correlate significantly with the anthropometric parameters of patients. Conclusion: Kidney size of patients with CKD correlated significantly with kidney function, while correlation with anthropometric parameters, which is otherwise present in healthy subjects, was lost in patients with CKD.